Pathways for sexual health promotion among Indigenous boys and men: stakeholder perspectives. (September 2021) - Biderman, Maya; Doria, Nicole; Sinno, Jad; Rand, Jenny Rebekah; Hackett, Lisa; Miller, Arthur Dave; McMillan, Jane; Lekas, Scott; Numer, Matthew
The sexual health of Indigenous Peoples in Canada has been identified as an important community and public health concern; however, there is a lack of research on the sexual health needs of Indigenous boys and men. This article shares results from interviews conducted with six stakeholders to explore pathways for sexual health promotion and considers the impacts of colonialism and other socio-political contextual factors on Indigenous boys' and men's sexual health. The study employed thematic analysis, and the findings indicate the following three pathways for sexual health promotion of Indigenous boys and men: (1) developing healthy relationships and highlighting role models, (2) providing access to comprehensive sexual health information, and (3) fostering open communication among Indigenous boys and men. Sexual health promotion with Indigenous boys and men in Atlantic Canada should include addressing the impacts of colonization and their unique socio-cultural contexts.